Catalytic Intermolecular Alkene Oxyamination with Nitrenes. Issue 29 (17th June 2014) - Dequirez, Geoffroy; Ciesielski, Jennifer; Retailleau, Pascal; Dauban, Philippe
Abstract The RhII‐catalyzed intermolecular addition of nitrenes to aromatic and aliphatic alkenes provides vicinal amino alcohols with yields of up to 95 % and complete regioselectivity. This 1, 2‐oxyamination reaction involves the formation of an aziridine intermediate that undergoes in situ ring opening. The latter is induced by the Rh‐bound nitrene that behaves as a Lewis acid.